Al-Qur’an dan Implementasi Pendidikan Karakter Kewarganegaraan - Gunawan Ikhtiono (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
This article would like to affirm that the cornerstone which strengthen civic education is al Qur’an surat An-nissa paragraph 59. There is a parallel between the line of command to obey the State Religion by obeying. This Islamic doctrine does not differentiate between the rights of the State and the religious right, as long as it’s still in/not contrary to Sharia, any attempt to shape need not be contentious. As for the educational value of the characters contained in the Quran as the character of faith, values, character of affection, gentle, urbane, togetherness, responsibility, patience, tawadlu imaniyah, simple, grateful, thankful, tawwakul, openness, love, hard work, creative, disciplined. The estuary from the application of all karkater it is the realization of a State Baldatun toyibun warafun ghofur. A good country and full of peace, full of forgiveness, people enjoy life and practice their religion quietly. Gemah Ripah Loh Jinawi, Toto Tentrem Kerto Raharjo. Prosperity, prosperity, and self-reliance of communities based on Pancasila that his grades based on the Quran and the Hadith, the Prophet. Then pass it the grace to the whole world, Rahmatan lil ‘ alamin.